Business Cycle Fluctuations, Large Shocks, and Development Aid : New Evidence - Dabla-Norris, Era (IMF Working Papers; Working Paper ;, 2010)
We examine the cyclical properties of development aid using bilateral data for 22 donors and over 100 recipients during 1970?2005. We find that bilateral aid flows are on average procyclical with respect to business cycles in donor and recipient countries. However, they become countercyclical when recipient countries face large adverse shocks to the terms-of-trade or growth collapses-thus playing an important cushioning role. Aid outlays contract sharply during severe donor economic downturns; this effect is magnified by higher public debt levels. Additionally, bilateral aid flows are higher in the presence of IMF programs and are more countercyclical for recipient countries with stronger institutions.